Publisher Correction: Towards quantitative and multiplexed in vivo functional cancer genomics. Issue 12 (December 2018) - Winters, Ian; Murray, Christopher; Winslow, Monte
The originally published article failed to acknowledge the equal first authorship contribution of I. P. Winters and C. W. Murray. The article has now been corrected online. The editors apologize for this error.